Determining Supply Chain Network Using Location, Invetory, Routing Problem (LIRP) Approaches. Issue 1 (June 2021) - Meutia, Sri; Anshar, Khairul; Subhan
Abstract: This research is motivated by the large number of complaints of the poor and micro-scale industries that have to buy 3 kg of LPG gas above the highest retail price set by the Aceh Government, Rp. 18, 000. There are several cases where people have been forced to buy at almost double the price (> Rp. 30, 000). One of the main causes of this spike is the unavailability. To ensure the availability of these goods, it is deemed necessary to establish a goods management policy (logistics system) which includes decisions on the allocation of goods distribution, inventory policies of all entities in the system being observed, and their delivery routes. With the formulation of an optimal goods management policy, it is considered to ensure the availability of goods which will lead to an appropriate selling price and, no less important, to reduce the management cost which has the effect of reducing the need for subsidies that must be issued by the government. The model used as a problem solving tool for the integration model of determining the location, inventory policy, and allocation delivery routes is classified as a Location-Inventory-Routing Problem (LIRP). The LIRP model is then performed optimization to determine which agents should operate, inventory policies at agents and bases, and delivery routes. From the model developed, it was concluded that only one operating agent was needed to supply 3 kg LPG gas, which served all bases operating in six villages in Muara Dua District, Lhokseumawe City.